(untitled) (Research, Society and Development, 2021)
The Covid-19 pandemic presents itself as one of the greatest health challenges of this century, generating an unprecedented crisis in public health in Brazil, and from the proliferation of this virus, a widespread panic has spread, where thousands of people have been affected by disturbances. psychological, having as main target the female audience. Faced with the state of public calamity, the Ministry of Education decreed new ordinances, and it was necessary for educational institutions and their educators to create strategies to promote distance education. In view of this problem, and to achieve the general objective of this research, a study will be carried out based on the structuring of a literature review and data analysis, on the impacts of the pandemic on mental health, especially on women who work in the education. To carry out this study, the deductive method and approach was used, in depth this research was constituted through exploratory research through the collection of bibliographic data of a qualitative and descriptive nature. The results found point to a psychological impact on the health of women who work in education, arising from emotional problems, resulting from the situation caused by the Covid-19 pandemic, where they often need to deal with the pressure of education systems, combined with the double journey of this situation may lead to psychological fragility, contributing to a worsening of mental health. In this sense, it is necessary to think, plan and implement actions to support mental health with more frequent psychosocial care for these professionals.